Dephosphorization of high silicon hot metal based on double slag converter steelmaking technology. (21st April 2021) - Dai, Yuxiang; Li, Jing; Shi, Chengbin; Yan, Wei
ABSTRACT: The average silicon content of the hot metal produced by Corex furnace is 0.6–1.5 mass%, which increases the oxygen blowing time and leads the unsatisfactory dephosphorization, high reblowing rate. The oxidation of carbon and silicon and optimization of dephosphorization during the refining process were studied through industrial practice and theoretical calculation. The results show that the optimum residual content of silicon in liquid steel at first slag making phase is about 0.05–0.07 mass%. The phosphorus content of liquid steel at first deslagging can be controlled at a low level (0.055–0.060 mass %), when the temperature is 1340–1360°C. The slag basicity of first deslagging should be controlled about 1.5, and (FeO) content should be controlled within 15%. In order to control the [P] of molten steel within 0.01mass%, the basicity should be higher than 3.4 and the temperature should be less than 1640°C.